2013
DOI: 10.4236/aid.2013.31006
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic and Clinical Comparison of Patients Harboring <i>Escherichia coli</i> Blood Isolates with and without Extended-Spectrum <i>β</i>-Lactamases

Abstract: The clinical and microbiologic characteristics of 34 patients with extended-spectrum β-lactamase (ESBL) positive E. coli isolated from blood were compared to 66 bacteremic patients with ESBL negative E. coli, from January 2007 through December 2009. Of the 21 ESBL positive isolates available for PCR analysis, 13 were positive for CTX-M, 8 for TEM, 4 for SHV β-lactamases, with 6 possessing multiple enzymes. Twenty of 34 (59%) ESBL-positive and 41 of 66 (62%) ESBL-negative blood isolates were considered communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, only five studies could be included in the meta-analysis; they reported total LOS results as a mean with standard deviation [ 40 , 75 , 89 , 92 , 95 ]. Eight studies could not be included in the meta-analysis because they reported total LOS using a median and interquartile range [ 74 , 90 , 94 , 97 , 99 ], or did not consistently report both a measure of central tendency and variability [ 43 , 88 , 108 ]. The five included studies reported an increase in the mean LOS in the third-generation cephalosporin-resistant patients compared to third-generation cephalosporin-susceptible patients, and the mean difference was significant in four of the five studies.…”
Section: Results Of Individual Studies Synthesis Of Results Risk Ofmentioning
confidence: 99%
“…However, only five studies could be included in the meta-analysis; they reported total LOS results as a mean with standard deviation [ 40 , 75 , 89 , 92 , 95 ]. Eight studies could not be included in the meta-analysis because they reported total LOS using a median and interquartile range [ 74 , 90 , 94 , 97 , 99 ], or did not consistently report both a measure of central tendency and variability [ 43 , 88 , 108 ]. The five included studies reported an increase in the mean LOS in the third-generation cephalosporin-resistant patients compared to third-generation cephalosporin-susceptible patients, and the mean difference was significant in four of the five studies.…”
Section: Results Of Individual Studies Synthesis Of Results Risk Ofmentioning
confidence: 99%